Factors Associated with Development of Ventral Hernias and Healthcare Seeking Behaviors in a Cohort of Pakistani Women - Vishal Farid Raza; M. Shabbir Chohan; Absar Nazir; Samiha Choudhry; Rabia Ammarah; Maham Latif; K.J.Khan, Khalid Irshad (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Anterior abdominal wall hernias constitute one of the most common surgical presentations. According to the World Bank data Pakistan has one of the highest birth rates per woman in the region at 3.6 births per woman. In Pakistan there has also been a large increase in C-section rates with nearly 20% of all pregnancies being delivered via C-section, nearly 1 out of every 5 births. Multi-parity is a risk factor for developing paraumbilical hernias and C-sections lead to incisional hernia developments. Methodology: The study conducted was a cross-sectional study at a tertiary care hospital in the department of surgery from 1st June 2021 till 1st September 2021. Any woman presenting with a ventral hernia to the clinic was asked to fill out a questionnaire. 60 women presented over the study period and were enrolled. Results: Fifty five percent paraumbilical hernias and 41.7% incisional hernias were reported. The mean number of pregnancies was 4.10 S.D 1.531 with a range from 0-8. C-sections were 2 times more common than SVDs. Increasing number of pregnancies associated with younger age of onset. Higher number of vaginal deliveries and C-sections were each associated with the development of a ventral hernia. Conclusion: The high fertility rate and C-section rate in Pakistan incurs a huge risk to women developing ventral hernias and poses a burden to the public healthcare system